Indoleamine 2,3‐dioxygenase 1 in coronary atherosclerotic plaque enhances tissue factor expression in activated macrophages - Watanabe, Yuki (Res Pract Thromb Haemost, 2018)
BACKGROUND: Recent clinical studies have found that changes in the kynurenine (Kyn) pathway of tryptophan (Trp) metabolism are associated with cardiovascular events. However, the roles of the Kyn pathway on vascular wall thrombogenicity remain unknown. Indoleamine 2,3‐dioxygenase 1 (IDO1) is a rate‐limiting enzyme of the Kyn pathway. OBJECTIVE: The present study aimed to localize IDO1 in human coronary atherosclerotic plaques from patients with angina pectoris and define its role in plaque thrombogenicity. METHODS: Immunohistochemical methods were applied to localize IDO1 in coronary atherosclerotic plaques from patients with stable (SAP) and unstable (UAP) angina pectoris. The role of IDO1 in tissue factor (TF) expression was investigated in THP‐1 macrophages activated by interferon (IFN)γ and tissue necrosis factor (TNF)α. RESULTS: We localized IDO1 mainly in CD68‐positive macrophages within atherosclerotic plaques, and in close association with TF. Areas that were immunopositive for IDO1, TF, and CD3‐positive T lymphocytes were significantly larger in plaques from patients with UAP than SAP. Macrophages activated by IFNγ and TNFα upregulated IDO1 expression, increased the Kyn/Trp ratio and enhanced TF expression and activity, but not TF pathway inhibitor expression. The IDO1 inhibitor epacadostat significantly reduced the Kyn/Trp ratio, TF expression and activity, as well as NF‐κB (p65) binding activity in activated macrophages. Inhibition of the aryl hydrocarbon receptor that binds to Kyn, also reduced Kyn‐induced TF expression in activated macrophages. CONCLUSION: Indoleamine 2,3‐dioxygenase 1 expressed in coronary atherosclerotic plaques might contribute to thrombus formation through TF upregulation in activated macrophages.